An efficient iron catalyzed regioselective acylative cleavage of ethers: scope and mechanism. Issue 51 (23rd December 2015) - Bodduri, V.D. Vijaykumar; Choi, Kyung-Min; Vaidya, Raghavender Rao; Patil, Kalpesh; Chirumarry, Sridhar; Jang, Kiwan; Yoon, Yong-Jin; Falck, John R.; Shin, Dong-Soo
Graphical abstract: Abstract: A method involving iron catalyzed acylative cleavage of cyclic and acyclic ethers with acyl/aroyl chlorides has been studied to produce chloroesters and esters respectively. Examination of the scope revealed that less electron rich alkyl group in unsymmetric, acyclic ether was acylated while the chloride derived from the counterpart moiety was volatile and difficult to isolate. In contrast, α-branched cyclic ethers were converted to the corresponding primary ester and secondary chloride. Steric hindrance of ether also plays an important role in acylative C–O bond cleavage. The mechanism of ether cleavage is proposed to involve a single electron initiated SN 1 dissociative pathway.